Findings of trans-fontanel echography in children with open fontanel and associated risk factors - Andrés Fabián Gualpa Jácome; Bárbara García Hernández; Diana Elizabeth Belnalcázar Villacreces; Alexis Rodríguez Hernández; Olga Lidia Fernández Chongo; Tahimí Conde Cueto (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: the use of ultrasound in pediatrics favors the primary diagnosis of some diseases. Trans-fontanel ultrasound is the most used to detect intracranial disturbances. Objective: to identify the type of ultrasound finding in children with open front fontanel and associated risk factors. Methods: decriptive study realized at the Pediatric Hospital of Cienfuegos from January 2014 to January 2015. All patients with open front fontanel and indicated trans-fontanel ultrasound were included. Children´s age and sex were analyzed and mother´s age, pregnancy complications, type of delivery and its complications, anatomic intracerebral variants and malformations as well. Results: 221 patients were studied between 1 and 24 months old with a mean of four months; 59.3% were male; ultrasonography disturbances in 21,3% (66% male). Ventricular Asymmetry was the most frequent anatomic variant. (6.8%) followed by benign macro-cephalic (5.9 %) and cavum septum pellucidum (4,1 %). The main malformation was mega cisterna magna (1,4 %) followed by subependymal cyst (0, 5 %). Dystocic delivery and maternal arterial hypertension, prematurity and hypoxic ischemic disease were the most frequently observed risk factors. Conclusion: brain ultrasonography is a useful, non-invasive method of easy interpretation for the early determination of nosology conditions of children, while the front fontanel is still opened. The interaction of risk factors in the mother so as in the child influence in the appearance of intra-cerebral malformations.